A Comprehensive and Extended Review of Volleyball Instructional Innovation and Extracurricular Development Across Indonesian Schools: A Synthesis of Soft-Ball Media Research and High-School Extracurricular Implementation - Juan Fidel Siahaan,; M.Mutawalli Shodiq,; Jahroniansyah,; Haikal,; Rifki Gamal Hasan,; Randi Kurniawan,; Deni Rahman Marpaung, (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
Volleyball learning in Indonesian educational institutions requires systematic pedagogical support, developmentally appropriate resources, and structured extracurricular pathways to ensure the progressive acquisition of psychomotor, cognitive, and affective competencies. This extended review synthesizes two major empirical studies focusing on volleyball learning across different educational levels: the development of instructional soft-ball media suitable for elementary students, and the implementation of volleyball extracurricular programs in senior high schools. The review adopts a narrative synthesis approach and presents an expanded discussion on research methodology, pedagogical relevance, contextual challenges, and systemic implications. Findings from the soft-ball development study demonstrate significant improvements in safety, engagement, motor coordination, and basic technical volleyball proficiency among young learners. Meanwhile, the qualitative study on volleyball extracurricular programs illustrates the effectiveness of structured training, the adequacy of facilities, and the level of student readiness for higher-level volleyball participation. The integration of both studies highlights the need for age-appropriate instructional media, improved teacher competence, better facility management, and sustainable program planning. This extended review contributes to volleyball education research by offering a consolidated perspective that bridges instructional innovation with extracurricular development across multiple schooling levels in Indonesia. Recommendations for policy, pedagogy, and future research are articulated to support long-term sport education development.Keywords: Volleyball education; instructional media; soft-ball development; extracurricular sports; motor coordination; physical education; learning innovation